Comparing the websites of top Iranian and international academic libraries from the standpoint of SEO and visual complexity - Maryam Tavosi; Nader Naghshineh; Mohammad Zerehsaz; Siamak Mahboub (مجله علم‌سنجی کاسپین)
Background and aim: One of the factors that affects the aesthetics of a website and attracts more users in the web environment is "visual complexity". The present research analyzed the correlation and regression between the SEO score and the level of visual complexity of the library websites of the top Iranian and international universities. Materials and methods: A comparative evaluation approach was adopted in this research. 41 library websites of top international universities (based on University Ranking 2023) and 41 library websites of top Iranian universities (based on ISC database 2021) were analyzed and compared. AIOSEO Analysis tool and Athec Python library were used for data extraction. SPSS was used for data analysis. Figures were generated using Excel. Findings: There was no significant correlation and regression between SEO and visual complexity on library websites of top international universities (p=0.125). However, on library websites of top Iranian universities, there was a weak correlation (p=0.045; Pearson correlation coefficient=0.362) and a significant regression (p=0.045). According to the Mann-Whitney U test, a significant difference was seen between the two groups of library websites of top Iranian and international universities from the standpoint of visual complexity (p=0.019). Conclusion: While top international academic libraries can rely on their strong branding, Iranian university libraries need to focus on both aesthetics and SEO to improve their visibility. Thus, using the experiences and knowledge of expert librarians in the fields of "SEO" and "aesthetics" is recommended.